A systematic comparison of the potential of microalgae-bacteria and purple phototrophic bacteria consortia for the treatment of piggery wastewater. (March 2019) - García, Dimas; de Godos, Ignacio; Domínguez, Christian; Turiel, Sara; Bolado, Silvia; Muñoz, Raúl
Graphical abstract: Highlights: Photosynthetic bacteria and microalgae provided similar wastewater treatment. Phototrophic bacteria exhibited higher organic carbon removal than microalgae. HRT governed pollutant removal and biomass productivity in both photobioreactors. Microalgae and bacteria population structure were determined by HRT. Abstract: This study evaluated the performance of two open-photobioreactors operated with microalgae-bacteria (PBR-AB) and purple photosynthetic bacteria (PBR-PPB) consortia during the treatment of diluted (5%) piggery wastewater (PWW) at multiple hydraulic retention times (HRT). At a HRT of 10.6 days, PBR-AB provided the highest removal efficiencies of nitrogen, phosphorus and zinc (87 ± 2, 91 ± 3 and 98 ± 1%), while the highest organic carbon removals were achieved in PBR-PPB (87 ± 4%). The decrease in HRT from 10.6, to 7.6 and 4.1 day caused a gradual deterioration in organic carbon and nitrogen removal, but did not influence the removal of phosphorus and Zn in both photobioreactors. The decrease in HRT caused a severe wash-out of microalgae in PBR-AB and played a key role in the structure of bacterial population in both photobioreactors. In addition, batch biodegradation tests at multiple PWW dilutions (5, 10 and 15%) confirmed the slightly better performance of algal-bacterial systems regardless of PWW dilution.